Siloxanes synthesized “in situ” by sol–gel process for fire control in wood of Araucaria angustifolia - Giudice, Carlos Alberto (2013)
Panels of Araucaria angustifolia were chemically modified with alkoxysilanes, hydrolyzed and condensed “in situ” by the sol–gel process. Alkoxysilanes selected were aminopropyl methyldiethoxysilane (A), aminopropyl triethoxysilane (B) and a mixture of both (C). Ethanol was used as solvent in 4/1 ethanol/ alkoxide molar ratio. The pH was adjusted to alkaline value for controlling the kinetic of hydrolysis– condensation reactions. Impregnation process was carried out at 45–50 1C in an autoclave, controlling the operating conditions for achieving different weight gains. Laboratory tests were carried out in Two-Foot Tunnel (flame spread index, panel consumption and smoke density) and in TGA detector (mass loss). The performance in laboratory tests can be explicated according the reactivity of the alkoxides. The results support the conclusion that the best fireproof efficiency was observed in woods treated with the alkoxide B, followed by those modified with the mixture C and the alkoxide A, in this order; the results also indicates that as weight gain increased the performance of impregnants against fire.